The Effect of Customary Law on Catch Share System in Fisheries, A Cause Study : In Muara Angke, Jakarta - Etty Eidman (Buletin Ekonomi Perikanan, 1993)
Factors controling the practice of catch sharing system of fishing community in Muara Angke, lire .rlutlv trrecr, were studied employing observation approach. It was found in this investigation that traditional norms (custom) has been more ifluencing in the practice of catch sharing in the community than the official law (Catch sharing Iaw No. 16/1964). In edition, the sharing system has also been influenced, in less degree, by fishing gear types and education level of the fishermen.